Factors Affecting the Technical Efficiency of Cassava Farming in Wonogiri Regency - Fitria Cahyaningsih, Anggi; Rahayu, Endang Siti; Kusnandar (Jurnal Manajemen & Agribisnis, 2022)
Cassava is a potential commodity to develop because it is used for consumption and industrial raw materials. Wonogiri Regency has the highest harvest and production area in Central Java. Such a high production level is not comparable to a low level of productivity. The productivity of cassava in Wonogiri Regency is only 18.99 tons per hectare lower than the national productivity, which is 25.95 tons per hectare. Therefore, it is necessary to use inputs as an efficient resource to increase productivity. This study analyzed the technical efficiency and factors affecting the efficiency of cassava. Primary data from 75 cassava farmers in Wonogiri Regency. Data Envelopment Analysis (DEA) and regression Tobit were the data analysis methods. DEA results showed efficiency scores ranging from 0.107 to 1.28% of cassava farmers in Wonogiri were technically efficient in carrying variable return to scale, with an average score of 0.580. Cassava farmers in Wonogiri Regency should increase the efficiency value by reducing slack inputs, namely cassava seeds, phonska fertilizer, and urea fertilizer. Tobit regression results show that farmer education and group membership significantly affect the efficiency of cassava. Farmers with higher education have better skills to adopt new technologies and use inputs more efficiently. The farmer group has a positive influence because it can provide information and discussion to overcome the problem of cassava farming. Keywords: cassava farming, DEA, efficiency, productivity, tobit regression